Life stressors, hypertensive disorders of pregnancy, and preterm birth. (2nd January 2022) - Morgan, Nathaniel; Christensen, Kylie; Skedros, Gregory; Kim, Seungmin; Schliep, Karen
Abstract: Background: Stress-induced pregnancy complications are thought to represent a significant cause of maternal morbidity and mortality; little is known regarding types of stress most predictive of adverse outcomes. Methods: We used Utah PRAMs 2012–2014 data to evaluate links between preconception life stressors and prevalence of hypertensive disorders of pregnancy (HDP) and pre-term labor (PTB) (births <37 weeks gestational age, and very PTB <33 weeks). We categorized 12 specific stressful events into 4 groups: partner, traumatic, financial, and emotional. Adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs) were estimated controlling for important sociodemographic, lifestyle, and pregnancy history factors. Results: 4, 378 mothers completed the survey. 26.6%, 12.2%, 32.2%, and 28.4% reported partner, traumatic, financial, and emotional-related stress. Reporting any of the 4-types of life stress was linked with increased prevalence of HDP (aPR: 1.46 [95% CI: 0.96, 2.22]) after adjusting for age, race/ethnicity, BMI, education, prior diagnosis of high blood pressure, and prior history of preterm labor. The strongest association was observed for financial stress (aPR: 1.50 [95% CI: 1.03, 2.18]). Financial stress was also associated with increased prevalence of very PTB (aPR: 1.61 [95% CI: 1.03, 2.51]) after adjustment. Conclusion: Women reporting financial stress, including job loss, pay reduction, or difficulty paying bills, had increased prevalence of HDP and very PTB.